LEADERSHIP PERFORMANCE AND INNOVATIVE WORK BEHAVIOR: A DATA-DRIVEN REVIEW FROM SCOPUS AI - Azfahanee Zakaria; Sarah Sabir Ahmad; Nurdiyana Nazihah Zainal; Nurin Azni Naila Mohd Farouk (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Leadership plays a crucial role in fostering innovation and enhancing employee performance, yet the specific leadership styles that drive innovative work behavior remain underexplored. This study aims to examine the impact of transformational, empowering, and inclusive leadership on employee creativity and innovation. Using a thematic analysis approach, emerging themes were identified from existing literature, highlighting consistent and rising trends in leadership effectiveness. The findings reveal that transformational leadership consistently enhances employee engagement and psychological empowerment; while empowering and inclusive leadership are gaining recognition for fostering autonomy and psychological safety. Additionally, high-performance work practices (HPWPs) were found to significantly contribute to innovation. These insights have both theoretical and practical implications, reinforcing leadership theories and guiding organizations in developing leadership strategies that cultivate a culture of innovation. Future research should explore the influence of digital transformation and cultural factors on leadership effectiveness.